A simple, accurate, and universal method for characterizing and comparing radiative cooling materials and devices. (January 2023) - Fan, Fan; Xu, Dikai; Zhu, Yazhu; Tan, Gang; Zhao, Dongliang
Abstract: Radiative cooling has emerged as a promising cooling technology for its potential in reducing energy consumption and carbon emissions. Remarkable progress has been made, and numerous novel materials have been designed and fabricated. However, different researchers adopted different homemade temperature measuring devices, making it difficult to compare the reported sub-ambient temperature drops since the thermal properties of different temperature measuring devices vary largely from one another, especially the non-radiative heat transfer coefficient. In this work, we propose a simple, accurate, and universal method to quantify non-radiative heat flux and non-radiative heat transfer coefficient of measuring devices, and compare them with the traditional method adopted in literature. The proposed method uses two identical measuring devices to measure the sub-ambient temperature drop and the net cooling power simultaneously to derive non-radiative heat transfer coefficient. To characterize and compare the thermal performance of a radiative cooling material or device, we recommend that both maximum sub-ambient temperature drop and non-radiative heat transfer coefficient should be reported. It is worth noting that the proposed method can obtain non-radiative heat transfer coefficient with high accuracy and it is not affected by weather conditions.